Move and Construal Examined: A Case Study With Tough Constructions - Kawai, Michiya (Linguistica Atlantica, 2004)
This paper studies Hornstein’s (2001) proposal that construal in natural language involves movement (construal-as-movement [CAM]), by examining the CAM analysis of tough constructions. The CAM analysis suffers because (a) it necessitates the global evaluation of derivational economy, (b) it is incompatible with the fact that tough-infinitives may be AP-internal, (c) it predicts the parallelism between tough-constructions and infinitival relatives, contrary to the fact, and (d) its treatment of Case is problematic. Finally, 1 briefty present a non-CAM analysis where the problems that arise with the CAM approach disappear. Although this study is primarily concerned with the CAM analysis of tough-constructions, the problems found herein reftect the problems of the CAM approach in general.